Correlation of Bone Mineral Density with Pulmonary Function in Advanced Duchenne Muscular Dystrophy. Issue 2 (12th June 2020) - Lee, Jang Woo; Cho, Han Eol; Kang, Seong‐Woong; Choi, Won Ah; Suh, Mi Ri; Kim, Bitnarae
Abstract : Background: A relationship between bone mineral density (BMD) and physical function has been revealed in the general population and various diseases. However, there is a lack of research investigating the correlation between BMD and respiratory function, one of few measurable physical parameters in patients with advanced Duchenne muscular dystrophy (DMD). Objective: To determine whether pulmonary function parameters, including respiratory muscle strength, are related to BMD. Design: Retrospective observational study. Setting: A tertiary university hospital. Patients: DMD patients who were over 20 years of age, nonambulatory, and supported by mechanical ventilators. Methods: The patients' age, weight, and pulmonary function as well as the BMD of the first and the fourth lumbar vertebra were assessed. Pulmonary function includes forced vital capacity (FVC), unassisted and assisted peak cough flow (UPCF and APCF), maximal expiratory pressure (MEP), and maximal inspiratory pressure (MIP). Main Outcome Measures: A bivariate correlation for BMD and other pulmonary parameters was calculated, and hierarchical regression analysis was used to determine predictors of spine Z‐score. Results: It was observed that the decrease in the spine BMD was not significantly correlated with age. However, the body mass index (BMI) and all parameters of pulmonary function were correlated with BMD. Partial correlation analysis adjusted by BMI showed that UPCF and APCF were powerful predictors of spine BMD. Conclusions: The BMD of the lumbar spine correlated with BMI and PCF in patients with DMD at an advanced stage.